(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
استهدف البحث التعرف على واقع البرنامج الإرشادي الموجه للمرأة الريفية في محافظة اللاذقية من خلال التعرف على الخصائص الشخصية للنساء الريفيات الملتحقات بأنشطة هذا البرنامج الإرشادي الموجه للمرأة الريفية, والتعرف على المواضيع التي تتناولها أنشطة البرنامج ومكوناته، وكذلك التعرف على المعوقات التي تواجه النساء الريفيات المشاركات في البرنامج ,ومقترحاتهن لإيجاد الحلول لها. ولتحقيق أهداف البحث تم تصميم استمارة استبيان بالمقابلة الشخصية , بلغ حجم العينة /200/ امرأة ريفية من محافظة اللاذقية . أوضحت النتائج أن 76.5 % من النساء المستهدفات هن من المتعلمات , و أهم الأسباب التي دفعت النساء لحضور الأنشطة هي حب المعرفة و الاطلاع و اكتساب مهارات و معارف جديدة ( 82%), وأهم الصعوبات التي تواجه تطبيق أنشطة البرنامج الإرشادي هي عدم توفر الإمكانيات المادية و غياب التمويل و صعوبة التسويق (34.7%), ومن أهم الأسباب التي تعيق إقبال المرأة الريفية على أنشطة البرنامج الإرشادي هي عدم توافر الوقت والانشغال بأعمال أخرى (63%). The research aimed to identify the status of the extension program for rural women in Lattakia governorate by examining the personal characteristics of the rural women who are involved in the activities of the extension program; and revealing the themes of these activities, their components, the problems that faced rural women, and their suggestions to resolve these problems. To achieve the aims of the research, we designed a questionnaire by personally interviewing 200 rural women from Lattakia Governorate. The results showed that 76.5% of the women who were the target of the research were educated. The most important reasons for the women to come to the activities are their love for knowledge and their eagerness to receive new skills and new information (82%). The most important difficulties that face the application of the program activities are the absence of resources, the lack of funding, and the difficulties in marketing (34.7%). The most important reasons that hinder the involvement of the rural women in the activities of the extension program are the lack of time and their preoccupation with other works (63%).